Gender equity: illusion or reality for women in the federal executive service? - Dolan, Julie (2004)
With the passage of the Civil Service Reform Act in 1978, the federal government created the Senior Executive Service (SES) and formally committed the federal government to equal employment opportunity, advocating a "federal service reflective of the nation's diversity". Since then, women have made dramatic progress in the ranks of the SES. This research probes the following questions: Has women's advancement into the ranks of the SES been illusory or real? Are women simply being appointed to token positions to fulfill affirmative action goals? Or do they contribute to governance from real positions of power and influence? Using data from a recent survey of Senior Executive Service members, this research indicates that male and female members of the SES have almost identical responsibilities and, most interestingly, women executives rate themselves as relatively more influential than do their male colleagues. - Reproduced.
Keywords: Women in the civil service